UNSUR-UNSUR ADMINISTRASI PENDIDIKAN DI MIS AL HAFZA ISLAMIC GLOBAL SCHOOL Abyena Hafza1, Afrida Juliani2, Putri Rizky3, Mursal Aziz4 - Hafza, Abyena; Juliani, Afrida; Rizky, Putri; Aziz, Mursal (Jurnal Media Informatika, 2024)
This research is entitled